Spectroscopic, Thermal, Electrochemical, and Antimicrobial Studies of Mononuclear Manganese(II) Ditolyldithiophosphates - Ruchi Khajuria; Atiya Syed; Sandeep Kumar; Sushil K. Pandey (Bioinorganic Chemistry and Applications)
New complexes of manganese(II) corresponding to [{(ArO)2PS2}2Mn] and [{(ArO)2PS2}2Mn.nL] (Ar=o-,m-,p-CH3C6H4 and p-Cl-m-CH3C6H3; n=1, L = N2C12H8, N2C10H8; n=2, L = NC5H5, P(C6H5)3) have been synthesized and characterized by microelemental analyses (C, H, and N), magnetic susceptibility, molar conductance, thermogravimetric, cyclic voltammetry, and spectral analyses including ESI mass spectrometry, IR, and UV-visible. The presence of a four-and-six coordinated Mn atoms has been established in the complexes and adducts, respectively. Antimicrobial screening of the complexes against gram negative bacteria E. coli, K. pneumonia, and P. aeruginosa and fungus S. rolfsii has shown potential bioactivity.